Los ambientes de aprendizaje y el desarrollo cognitivo del infante. - Catucuamba Manobanda, Lilia Noemi (2018)
This research had as a reference the study of the learning environment and the cognitive development in Infants at "Plinio Robalino" School of Basic Education. It is located in Quito, Pichincha Province during 2017-2018. The objective of this research was to know how to expand children´s cognitive progress in each of the designated spaces with different purposes, taking advantage of time, space, flexibility, freedom and discipline to encourage creativity in a positive way in all students. The research aims to guide adequately the development of each learning environment, focusing on the fundamental areas such as spaces, resources and teachers to achieve the maximum children´s cognitive development using these educative corners. The methodology used in the research is descriptive because it was possible to focus on the importance of learning environment as a cognitive development tool, allowing the researchers to know the appropriate form to guide each of the educative corners. The use of this method allowed to do a diagnosis of the present problem with the use of interviews and surveys. The impact of this research is social because it allowed to know the importance of learning environment in the development of kindergartens; the learning environment will help to fortify children´s cognitive learning so they can achieve their autonomy and independence becoming a positive citizens who can interact in the society.In addition to, the research aims to guide the teacher and encourage the need to continuously train on the correct use of these learning environment with the application of new techniques, accurate and appropriate strategies to encourage infants to increase cognitive meta-development with the use of different educative corners and consolidate new knowledge to create affinities according to their development into the society.